Observation of Gonio Structures during Microhook Ab Interno Trabeculotomy Using a Novel Digital Microscope with Integrated Intraoperative Optical Coherence Tomography - Akiko Ishida; Kazunobu Sugihara; Tomoki Shirakami; Aika Tsutsui; Kaoru Manabe; Masaki Tanito (Journal of Ophthalmology)
Purpose. Observation of ocular structures using microscope-integrated intraoperative optical coherence tomography (iOCT) has been adopted. Using the novel digital ophthalmic microscope, ARTEVO 800 with iOCT, we tested the feasibility of trabecular meshwork (TM) imaging during microhook ab interno trabeculotomy, a minimally invasive glaucoma surgery. Methods. The nasal and temporal sides of the TM/inner wall of Schlemm’s canal were incised more than 3 clock hours in 14 glaucomatous eyes of 10 patients. To observe the trabeculotomy site, iOCT was performed with the real-time five-line scan mode under observation using a Swan-Jacob gonioprism lens. The success of the imaging and visibility of the trabeculotomy cleft and its incisional patterns (i.e., anterior, middle, or posterior pattern) were determined by reviewing the iOCT video files. Results. OCT images of the region of interest were acquired successfully in 100% of the 28 nasal or temporal sides in 14 eyes, although the trabeculotomy cleft was not visualized in four (14%) sides due to blockage of the OCT signal by a blood clot. Based on the predominant locations of the TM flaps in 24 of the acquired images, the trabeculotomy clefts were classified as anterior incisional patterns in 13 (54%), middle incisional patterns in nine (38%), and posterior incisional patterns in two (8%). Conclusion. Intraoperative imaging of the gonio structures including the trabeculotomy cleft was feasible using the ARTEVO 800 with iOCT in combination with a gonioprism.